Pulmonary Embolism: Webcast June 13 2024 - Alan B. Lumsden; Thomas M. Loh; Patrick E. Muck; Pavan Thangudu; Joseph J. Naoum; Nicolas J. Mouawad; Zachary Steinberg; Paul Haddad (Methodist DeBakey Cardiovascular Journal)
This 61-minute webcast features a conversation about “Pulmonary Embolism”—the focus of Issue 20.3. Hosted by the issue’s editors, the discussion engages the authors on emerging themes and lessons learned while researching and writing the articles. View the video at https://vimeo.com/1041707607.